Unleashing Customer Delight: The Dynamic Interplay of Product Excellence, Exceptional Service and Irresistible Prices - Tamon, Theo (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The growing and rapid need for internet access has sprung up many internet service providers other than GSM operators, where competing with each other to attract customers. This study aims to determine the effect of product quality, service quality and price on customer satisfaction. In this study using a population of 247,341 customers according to PT. Telkom Indonesia Telecommunication Business Area Tangerang using the slovin formula obtained a sample of 100 respondents, the data analysis technique used is a quantitative associative method with a verifiative approach. The results of the study prove that product quality has a positive and significant effect on customer satisfaction.